Gravity Disturbance Analysis of Geodynamics In East Indonesia - Al Shida Natul; Teuku Rykard Yudha Pratama; Annisa Kurnia Shalihat (Politeknik Negeri Batam, 2023)
Gravity satellites can be used for geodynamic studies in large and hard-to-reach areas. This study conducts gravity disturbance analysis from GOCE and EGM2008 satellite data for geodynamic interpretation in eastern Indonesia, the results of which are used as a basis for disaster mitigation. Gravity disturbance processing results from GOCE data with values around -300 to 260 mGal and EGM2008 with values around -350 to 450 mGal. Gravity disturbance maps of the GOCE and EGM2008 can clearly show fault patterns in the sea. However, the EGM2008 gravity disturbance map shows the fault pattern in the sea more clearly than the GOCE gravity disturbance map due to the higher spatial resolution of EGM2008 than GOCE. The cross-section of the GOCE and EGM2008 gravity disturbance maps represents the gravity signal of the study area; the GOCE graph represents the signal and forms the EGM2008 gravity disturbance signal components. The novelty of this research is related to the comparison of gravity disturbance maps from GOCE and EGM2008 data, which can be used to detect regional geological structures in eastern Indonesia.